An unprecedented CuII14TeIV10 core incorporated in a 36-tungsto-4-silicate polyoxometalate with visible light-driven catalytic hydrogen evolution activity. Issue 46 (11th October 2018) - Chen, Wei-Chao; Wu, Si-Tong; Qin, Chao; Wang, Xin-Long; Shao, Kui-Zhan; Su, Zhong-Min; Wang, En-Bo
Abstract : The first tellurous copper cluster embedded within tungstosilicate exhibiting visible light-driven catalytic H2 evolution activity has been obtained. Abstract : We report an unprecedented CuII14TeIV10 core containing the novel μ, μ-/μ6 -Te IV O3 2− mode and Te IV O4 4− embedded within a 36-tungsto-4-silicate POT shell, which constitutes the first example of a tellurous copper cluster in POMs. The structure-stabilizing and templating effects of tellurite anions are crucial for this assembly. Moreover, its visible light-driven catalytic H2 evolution activity and related quenching mechanism are demonstrated, and extensive stability studies are presented.